Dengue: multicentre clinical profile of patients admitted in intensive care unit - Rajender, Akash; C., Deepa; K., Krishna; Chaudhri, R. S.; R., Gaurav; C., Priyanka (International Journal of Research in Medical Sciences, 2016)
Background: Dengue with 2.5 billion people at risk and 50 million new cases every year is one of the most rapidly spreading vectors borne disease in world. We aimed to analyse the clinical profile of dengue patients requiring ICU admission. Methods: In a cross-sectional, observational, multicenter case study 105randomly selected laboratory positive dengue subjects were randomly selected from four tertiary care centers ICU’s. Socio-demographical, clinical, therapeutic & laboratory parameters were evaluated. Statistical analysis was done using SPSS version 14.0. Results: The main cause of ICU admission was shock or hypotension due to sepsis (20%). Most patients presenting complaint was fever (93.33%), bodyache (84.76%) and retro-orbital pain (34.3%). Most prevalent warning sign indicating severe dengue was abdominal pain (37.4%). Mucosal bleed (20.9%) was the most common haemorrhagic manifestation. 37.14% with warning signs and 62.86% patients with severe dengue required ICU care. Conclusions: A rapid assessment of clinical profile, presenting symptoms and warning signs can aid in early decision for requirement of ICU admission & may go a long way in decreasing mortality.